Heart rate variability is a moderating factor in the workload-injury relationship of competitive crossfit™ athletes - Williams, S.; Booton, T.; Watson, M.; Rowland, D.; Altini, M. (Journal of Sports Science & Medicine, 2017)
Heart rate variability (HRV) is a popular tool for monitoring training adaptation and readiness in athletes, but it also has the potential to indicate early signs of somatic tissue overload prior to the onset of pain or fully developed injury. Therefore, the aim of this study was to investigate the interaction between HRV, workloads, and risk of overuse problems in competitive CrossFit™ athletes. Daily resting HRV and workloads (duration × session-RPE) were recorded in six competitive CrossFit™ athletes across a 16 week period. The Oslo Sports Trauma Research Center Overuse Injury Questionnaire was distributed weekly by e-mail. Acute-to-chronic workload ratios (ACWR) and the rolling 7-day average of the natural logarithm of the square root of the mean sum of the squared differences between R-R intervals (Ln rMSSDweek) were parsed into tertiles (low, moderate/normal, and high) based on within-individual z-scores. The interaction between Ln rMSSDweek and ACWR on overuse injury risk in the subsequent week was assessed using a generalized linear mixed-effects model and magnitude-based inferences. The risk of overuse problems was substantially increased when a `low` Ln rMSSDweek was seen in combination with a `high` ACWR (relative risk [RR]: 2.61, 90% CI: 1.38 - 4.93). In contrast, high ACWRs were well-tolerated when Ln rMSSDweek remained `normal` or was `high`. Monitoring HRV trends alongside workloads may provide useful information on an athlete`s emerging global pattern to loading. HRV monitoring may therefore be used by practitioners to adjust and individualise training load prescriptions, in order to minimise overuse injury risk.